Baku mutu kualitas air muara sungai di kawasan Pura Petitenget dan upaya pengendaliannya - Suantara, Putu; Sudiana, A.A. Ketut; Sumantra, I.K (Institute for Advanced Science, Social, and Sustainable Future, 2024)
The main objective of this research is to analyze the quality standards for the quality of flowing water and river estuaries in the Petitenget Temple Area and efforts to control pollution or reduce the quality standards for flowing and river estuary water in the Petitenget Temple Area. The research was conducted from December 2018 to April 2019 in the river that flows into Petitenget Beach by taking four sampling points. The quality of water quality standards is measured using the water quality standards of Bali Governor Regulation No. 16 of 2016 concerning Environmental Quality Standards and Standard Criteria for Environmental Damage. The results of the research found that the quality of the water quality standards in the Petitenget Temple area had experienced pollution, namely the parameters of turbidity, chemical oxygen demand (COD), biological oxygen demand (BOD5), phosphate (PO4-P), total ammonia (NH3-N), fecal coliform, and total coliform. Efforts that can be made to overcome pollution in Loloan waters and river estuaries in Petitenget are the creation of Waste Management Regulations through the 4R (Reuse, Reduce, Recycle, Replace) pattern, limiting the use of chemical fertilizers and pesticides, creating waste storage and processing (septic tanks), and involving traditional villages (based on traditional villages) as well as environmental law enforcement.